Revolutionizing Glaucoma Care: Innovative Latanoprost Drug Delivery Takes Aim at Vision Loss (Asian Journal of Pharmaceutics (AJP), 2024)
Glaucoma remains one of the leading causes of irreversible blindness worldwide, presenting a significant publichealth challenge. Current glaucoma management primarily relies on eye drops, with prostaglandin analogs, suchas latanoprost being a cornerstone of treatment. However, patient adherence, ocular side effects, and the needfor consistent dosing pose substantial obstacles to effective care. This review paper introduces a groundbreakingapproach to glaucoma management through innovative latanoprost drug delivery. By leveraging cutting-edgedrug delivery technologies, including sustained-release systems and advanced ocular implants, this revolutionaryapproach aims to address the limitations of conventional eye drops and transform glaucoma care. In conclusion,the integration of innovative latanoprost drug delivery systems holds great promise for revolutionizing glaucomacare. These advancements offer the potential to significantly reduce the burden of vision loss associated withglaucoma and improve the quality of life for affected individuals. Further research and clinical trials are essentialto validate the safety and efficacy of these new approaches and usher in a new era of glaucoma management.